"Lingua receptiva" czy "lingua franca" - zachowania językowe mieszkańców polsko-czeskiego pogranicza = "Lingua receptiva" or "lingua franca" - language behaviour of the Polish-Czech borderland` habitants - Steciąg, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to analyse the problem of competition between or coexist- ence of ELF ("English as Lingua Franca") and LaRa ("Lingua Receptiva") as communication modes in the Polish - Czech border area. To support the analysis the questionnaire research have been conducted and the quantitave results are presented in the paper.
Keywords: zachowanie językowe; "lingua franca"; "lingua receptiva"; pogranicze polsko-czeskie; language behaviour; Polish-Czech borderland